2022
DOI: 10.1007/s10508-021-02244-w
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Difficulties, Problems, and Help-Seeking in a National Representative Sample: The Second Australian Study of Health and Relationships

Abstract: Richard (2022) Sexual difficulties, problems, and help-seeking in a national representative sample: the second Australian study of health and relationships. Archives of Sexual Behavior.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 41 publications
2
4
0
Order By: Relevance
“…With regard to the role of sexual problem symptoms, the findings are consistent with previous studies which have suggested that higher levels of sexuality-related personal distress as well as difficulties or pain with vaginal penetration are associated with higher help-seeking, whereas problems related to a lack of sexual desire are associated with lower help-seeking intention [ 25 ]. Informing women about their right to pleasure can strengthen their sense of entitlement to a satisfying sex life.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…With regard to the role of sexual problem symptoms, the findings are consistent with previous studies which have suggested that higher levels of sexuality-related personal distress as well as difficulties or pain with vaginal penetration are associated with higher help-seeking, whereas problems related to a lack of sexual desire are associated with lower help-seeking intention [ 25 ]. Informing women about their right to pleasure can strengthen their sense of entitlement to a satisfying sex life.…”
Section: Discussionsupporting
confidence: 88%
“…In a French GSSAB-sample, experiencing problems with lubrication was associated with more help-seeking behavior [ 24 ]. These findings are in line with a large population-based study among Australians showing that both pain during intercourse as well as lubrication problems were associated with more help-seeking behavior [ 25 ]. Overall, there appears to be evidence that sexual problems affecting vaginal intercourse, and thus may have a stronger impact on sexual behavior in heterosexual couples, result in more help-seeking compared with sexual problems affecting women’s personal sexual experience (e.g., low desire, lack of mental sexual arousal, or difficulty achieving orgasm).…”
Section: Introductionsupporting
confidence: 90%
“…In a recent Australian survey covering the age span 16 −69 years, 13.7% of men and 18.1% of women had not engaged in partnered sex in the previous year. 6 Presumably due to the broader age range of respondents in the present study, we observed somewhat higher proportions of inter-personal sexual inactivity (men: 23.0%; women: 28.8%). Such sexual inactivity was more common among participants with poor self-rated health and those with physical or mental disease in age-adjusted analyses.…”
Section: Inter-personal Sexual Inactivitymentioning
confidence: 43%
“…5 In Australia, sexual difficulties experienced for at least a month during the last year were reported by as many as 48% of men and 68% of women in a national survey, but large proportions of these difficulties were not perceived as problematic, thus failing to constitute sexual dysfunctions. 6 Associations between indicators of poor health and sexual problems have been the subject of several investigations. The British Natsal-3 survey demonstrated that a considerable proportion of sexual dysfunctions were associated with current health problems, 7 and links between erectile dysfunction and chronic conditions such as cardiovascular diseases and diabetes are wellestablished.…”
Section: Introductionmentioning
confidence: 99%
“…To these correspond the HSDD and the female sexual interest/arousal disorder, respectively. Research indicates that, when compared to men, women experience more sexual desire difficulties [ 7 , 16 ]. These are characterized by the lack of, or significantly reduced, sexual interest/arousal in almost all sexual encounters and the unreceptiveness to partner’s attempts to initiate sexual activity according to the DSM-5 [ 17 ].…”
Section: Introductionmentioning
confidence: 99%